Case report: Surgical management of a rare right coronary artery fistula with a giant pseudoaneurysm compressing the pulmonary vein in a young patient - Tang, Weijie; Xiang, Kun; Zhou, Huatao; Li, Yichen; Yang, Jinfu; Liu, Jijia; Fan, Chengming (Frontiers in Cardiovascular Medicine, 2023)
Congenital coronary artery fistula (CAF) represents a remarkable rarity within the realm of cardiovascular anomalies, characterized by an aberrant connection between coronary arteries and either cardiac chambers or major vessels. Clinical manifestations of CAFs often remain unspecified or may even be entirely absent, posing diagnostic challenges. Notably, patients harboring substantial CAFs may exhibit symptoms such as palpitations, chest tightness, and dyspnea. Although right-sided congenital CAFs are relatively prevalent, the occurrence of a CAF accompanied by a colossal pseudoaneurysm imposing compression upon the pulmonary vein is an exceedingly rare phenomenon. This exceptional case report delineates a singular fistula originating from the right coronary artery, extending its course to the right atrium, and remarkably featuring a substantial pseudoaneurysm exerting compression upon the right superior pulmonary vein. Therapeutic intervention encompassed surgical closure of the proximal artery and excision of the pseudoaneurysm, underscoring the complexity and criticality of managing such intricate cardiac anomalies to ensure optimal patient outcomes.